Investigating causal attributions of success and failure on mathematics instructions of students in turkish high schools - YAVUZ, İLYAS (ELSEVIER SCIENCE BV, 2010)
According to cognitive psychologists, student beliefs about their probability and causes for success and failure greatly influence their academic achievement. The aim of this study is to investigate causal attributions of success and failure on mathematics instructions of students in Turkish high schools. A questionnaire composed of 5-point Likert type questions was administered to 96 last year students who were enrolled in some public schools of Istanbul. The findings revealed that some attributions most frequently were observed as follows: differences between some situations used in everyday life and mathematics, insufficiency of mathematical textbooks to meet the students' needs, having the belief that mathematics is difficult due to student's previous experiences. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Causal attribution theories; mathematics education; succes and failure on mathematics; MOTIVATION